Viroinformatics study: polytope mapping of envelope glycoprotein to tackle HIV-2 infection and develop vaccine candidate - Kharisma, Viol Dhea; Widyananda, Muhammad Hermawan; Probojati, Rasyadan Taufiq; Ansori, Arif Nur Muhammad; Murtadlo, Ahmad Affan Ali; Tamam, Muhammad Badrut; Wicaksono, Adhityo; Turista, Dora Dayu Rahma (Generasi Biologi Indonesia, 2021)
Human Immunodeficiency Virus type 2 (HIV-2) has been identified to exhibit an ability to resist antiretroviral administration and many scientists has predicted increases in the pathogenicity of HIV-2. The development of a vaccine against the type 1 virus (HIV-1) infection has reached the phase 3 clinical trial stage, but currently there is no information on the development of a vaccine against HIV-2. Vaccine development to trigger an increase in the coverage of the expansion of protection can be done through B cell polytope. This study aims to provide an important preliminary for the construction of vaccine candidates by identifying the peptides that make up the B cell polytope in the HIV-2 envelope glycoprotein region. The HIV-2 sequence was obtained from the database. The study followed by 3D modelling, prediction of linear B-cell epitope mapping, antigenicity, allergenicity, peptide properties, and immune simulation was carried out via a webserver. The 3D structure of the peptide was displayed through molecular visualization software. The results showed that the 23-mer peptides E1 'HPRYTGVKNIRDITLTEPGRGSD', F1 'NFIENRKGTQHN' 12-mer, M1 'YLKDQARLNS' 10-mer, N1 'PWVNDSIQPNWNNMTWQQWELQVRD' 25-mer, and O1 'KLQNSWNMGVQTO' can be used as a candidate polytope HIV-2 vaccine because it is recognized by B cells is an antigenic peptide with stable molecule, non-allergenic. The peptides trigger proliferation and activation of B cells to produces a humoral response and work as functionally protective antibody for neutralization of HIV-2. Key words: Acquired Immune Deficiency Syndrome, B-cell, Bioinformatics, Human Immunodeficiency Virus, Retrovirus